2007
DOI: 10.1007/s00592-007-0238-6
|View full text |Cite
|
Sign up to set email alerts
|

The association between type 2 diabetes mellitus and A1/A2 polymorphism of glycoprotein IIIa gene

Abstract: Glycoprotein IIIa (GpIIIa) is a membrane receptor, found in various tissues, that has two alleles: A1 and A2. Signalling cascade of GpIIIa is modulated by enzymes called calpains, proteases that may also influence glucose metabolism. There is one small study that shows a high association of A1/A2 polymorphism with type 2 diabetes mellitus. In our research we planned to evaluate the association of A1/A2 polymorphism with type 2 diabetes in a population of patients with ST elevation acute myocardial infarction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…Analysis based on ethnicity was limited to Caucasians as the majority of studies did not explicitly state the ethnicity of participants. A non-significant pooled OR for the association of PlA2 carriage with MI was observed for the 11 available studies ( n  = 10,585; OR 1.050, 95% CI 0.962–1.146; p = 0.272) [71], [81], [88], [95]–[97], [103], [109], [112], [127], [128].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis based on ethnicity was limited to Caucasians as the majority of studies did not explicitly state the ethnicity of participants. A non-significant pooled OR for the association of PlA2 carriage with MI was observed for the 11 available studies ( n  = 10,585; OR 1.050, 95% CI 0.962–1.146; p = 0.272) [71], [81], [88], [95]–[97], [103], [109], [112], [127], [128].…”
Section: Resultsmentioning
confidence: 99%
“…Cohort studies did not demonstrate an association between carriage of the PlA2 allele and MI ( n  = 19,032; OR 0.996, 95% CI 0.917–1.082; p = 0.926) [80], [85], [86], [92]–[95], [97], [100], [105], [106], [109], [112], [114], [118], [125], [126], whereas case-control studies did ( n  = 21,660; OR 1.126, 95% CI 1.057–1.198; p<0.001) (Figure 6) [70]–[73], [81][84], [87][91], [96], [98], [99], [101][104], [107], [108], [110], [111], [113], [115][117], [119]–[124], [127], [128]. Studies with <250 cases showed a significant association ( n  = 10,145; OR 1.240, 95% CI 1.139–1.350; p = 0.006) [70], [72], [73], [80]–[83], [85], [88][94], [97], [98], [102], [103], [105], [108], [110], [111], [113][116], [118][127], [130], whereas studies with ≥250 cases did not ( n  = 30,547; OR 0.999, 95% CI 0.935–1.084; p = 0.864) …”
Section: Resultsmentioning
confidence: 99%
“…Following the activation of platelets by agonists such as ADP, thrombin, or collagen, inside-out 3 signaling occurs, giving rise to the exposure of the ligand binding site of GPIIb-IIIa. 17 The mentioned polymorphism can influence both platelet activation and aggregation 21 and affect postoccupancy signaling by the platelet fibrinogen receptor IIb/IIIa. 19,20 Both GPIIb and GPIIIa are known to bear a number of single amino acid substitutions affecting conformational changes and the ligand binding function with little or no effect on platelet function.…”
Section: Genetic Factors and Glycoprotein Iib-iiiamentioning
confidence: 99%
“…27 Studies on the association of the PlA1/ A2 polymorphism of glycoprotein IIIa and type 2 diabetes have reported conflicting results 17,28,29 (Table 54.6). It has been suggested that the function of platelet GPIIIa is modulated by a cysteine protease, calpain 10, which is not characteristic of platelets.…”
Section: Genetic Factors and Glycoprotein Iib-iiiamentioning
confidence: 99%
“…A platelet‐specific antigen (PlA1/A2) polymorphism has been by far the most investigated GPIIIa gene polymorphism. A substitution of cytosine for thymidine at position 1565 in exon 2 of GPIIIa gene leads to an amino acid difference at position 33: a leucine (A1 allele) or a proline (A2 allele) 1 . The mentioned polymorphism can influence both platelet activation and aggregation 10–12 and affect post occupancy signalling by the platelet fibrinogen receptor IIb/IIIa 13 .…”
Section: Introductionmentioning
confidence: 99%